The Effectiveness of Five-Finger Hypnotics on the Exponential Development of the First Stage of Labor in Primigravids - Jayanti, Nicky Danur (Jurnal Kesehatan - STIKes Prima Nusantara, 2023)
Background of the Problem: Childbirth is often something scary, especially for a woman who is pregnant for the first time (primigravida) and is about to give birth (primipara). There are several methods for physical and psychological readiness for pregnant women who will undergo labor, one of which is hypnosis. Hypnosis has been legally recognized by WHO as an alternative therapy. 5 finger hypnosis is able to provide deep relaxation, both physically, breath and mind so that in this state of deep relaxation it can activate the subconscious mind which will facilitate the creation of a relaxed atmosphere, stable, comfortable and happy emotions so that childbirth goes quickly.Objective: This study was conducted to determine the efficiency of 5 finger hypnosis on the acceleration of the first stage of labor in primigravida.Methods: The research design used a quasi-experimental design, namely using a post-test only design. The sample was 15 primigravida mothers with low risk pregnancies, the sampling technique used was purposive sampling. Bivariate data analysis, with testing using the Independent sample t-test statistical test.Results: The results of the analysis of the T-Test test with a value of Sig = 0.000 < = 0.05, this proves that there is an efficiency of the 5 finger hypnosis method on the acceleration of the first stage of labor in primigravida. 5 Finger Hypnosis works by influencing the hormone endorphins or referred to as the hormone of happiness. When the body feels relaxed and comfortable, the brain will secrete endorphins which will cause an analgesic effect so delivery is faster.Conclusion: 5 Finger Hypnosis in maternity mothers can help speed up labor by activating endorphins which are pain-relieving hormones, so this method is effective in eliminating all complaints and feelings of discomfort.